2021
DOI: 10.1007/s43039-021-00022-z
|View full text |Cite|
|
Sign up to set email alerts
|

Cultural dimensions in online purchase behavior: Evidence from a cross-cultural study

Abstract: The objective of this research is to investigate how cultural differences affect consumers’ online purchase behavior. We reviewed the recent literature on cross-cultural studies on online behavior and building on Hofstede’s theory of cultural dimensions and the theory of planned behavior (TPB), we developed a conceptual model exploring how the dimensions of national culture influence perceptions of website usability, trust, and perceived risk, which in turn impact on intention to use and online purchase behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 64 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…uncertainty avoidance was strongly correlated with intention to use online products, while European consumers were not (Pratesi et al, 2021). Similarly, researchers found significant differences within individualistic countries, such as consumers' intention to purchase across European nations, namely, Italy and Spain (Zollo et al, 2021).…”
Section: The Role Of Culturementioning
confidence: 95%
See 2 more Smart Citations
“…uncertainty avoidance was strongly correlated with intention to use online products, while European consumers were not (Pratesi et al, 2021). Similarly, researchers found significant differences within individualistic countries, such as consumers' intention to purchase across European nations, namely, Italy and Spain (Zollo et al, 2021).…”
Section: The Role Of Culturementioning
confidence: 95%
“…Scholars have traditionally recognized culture as a key variable to understand consumers' attitude, intention, and behavior. Recent research (Pratesi et al, 2021) shows how online purchase behavior differs across Asian and European markets, stressing the key role of culture as the main antecedent of consumers' intention to use and purchase online products. As a result, building on Hofstede's (2001) cultural dimensions theory, these authors found European consumers' individualism positively correlated with their intention to use online products, while no significant relation was found in the Chinese sample, which is a highly collectivistic country (Sivadas et al, 2008).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Business success is contingent upon the ability to attract consumers from international markets. Research has indicated that individuals from different countries exhibit distinctive decision-making styles [14,15] and purchasing behaviors [16,17] in the context of consumer purchase behavior. However, the current literature on consumer behavior toward handcrafted fashion products is lacking, particularly concerning international perspectives and the examination of eco-friendly alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…To fill these research gaps, the present study adopts a cross‐cultural perspective to investigate the effects of m‐commerce repurchase intention by comparing Asian and Western consumers. An Asian country, China, and a Western country, Italy, were chosen for two main reasons: (a) different cultural paradigms characterize Italy and China according to Hofstede's (1980) cultural value dimensions, that is, Italian consumers show a higher level of uncertainty avoidance, individualism, and masculinity, whereas Chinese ones display greater perceived power distance, and long‐term orientation (Pratesi et al, 2021); (b) Chinese consumers are heavier users of mobile devices for shopping reasons than Italian users.…”
Section: Introductionmentioning
confidence: 99%